(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
Brazil’s presidential elections held last October were the closest in the country’s history. The results reflect the polarized political environment and the scenario of political violence, institutional delegitimization, and social unrest perpetuated by the bolsonaristas, which reached its peak with the assault on the Palácio do Planalto This was the concluding act of a process of construction of dialectical and visual violence, steeped in denialism and delegitimization of the opponent. This led to a highly conflictual and aggressive electoral space, that institutions like the Tribunal Superior Eleitoral and Transparência Eleitoral Brasil tried to counter. This essay investigates the pre-and post-electoral violence and the role of the institutions designated to mitigate it.